MANAJEMEN PEMASARAN DALAM PROSES PENERIMAAN PESERTA DIDIK BARU DI MADRASAH ALIYAH NURUL IHSAN PENINJAUAN, KEC. MARO SEBO ULU, KAB. BATANG HARI - Zulkarnaini; Marwazi; MY, Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the implementation of marketing management in the new student admission process (PPDB) at Madrasah Aliyah Nurul Ihsan Peninjauan, Maro Sebo Ulu District, Batang Hari Regency. This qualitative study with a case study approach aims to analyze marketing strategies, identify supporting and inhibiting factors, and formulate strategic solutions to improve PPDB effectiveness. Data were collected through in-depth interviews with the madrasah principal, vice principal for student affairs, PPDB committee, teachers, students, and parents, complemented by participatory observation and documentation. Data analysis employed the interactive model of Miles, Huberman, and Saldaña. The findings indicate that PPDB marketing management is not yet optimal, with the implementation of the 7P marketing mix still being conventional. Supporting factors include HR commitment, strong Islamic values, community leader support, and affordable costs. Inhibiting factors include location limitations, promotional budget constraints, lack of marketing competence among HR, intense competition, limited facilities, and suboptimal utilization of digital technology. Recommended strategic solutions include social media optimization, official website development, HR training, development of superior programs, and establishment of an integrated marketing management system to enhance madrasah competitiveness in the long term.